Regional crustal and lithospheric thickness model for alaska, the chukchi shelf, and the inner and outer bering shelves - Torné, Montserrat; Jimenez-Munt, Ivone; Vergés, Jaume; Fernandez, Manel; Carballo, Alberto; Jadamec, Margarete (Geophysical Journal International, 2020)
This study presents for the first time an integrated image of the crust and lithospheric mantle of Alaska and its adjacent western shelves of the Chukchi and Bering seas based on joint modeling of potential field data constrained by thermal analysis and seismic data. We also perform 3D forward modelling and inversion of Bouguer anomalies to analyze density heterogeneities at the crustal level. The obtained crustal model shows northwest-directed long wavelength thickening (32 to 36 km), with additional localized trends of thicker crust in the Brooks Range (40 km) and in the Alaska and St. Elias ranges (50 km). Offshore, 28–30 km thick crust is predicted near the Bearing slope break and 36–38 km in the northern Chukchi Shelf. In interior Alaska, the crustal thickness changes abruptly across the Denali fault, from 34–36 to the north to above 30 km to the south. This sharp crustal thickness gradient agrees with the presence of a crustal tectonic buttress guiding block motion west and south towards the subduction zone. The average crustal density is 2810 kg∙m−3. The denser crust, up to 2910 kg∙m−3, is found south of the Denali Fault likely related to the oceanic nature of the Wrangellia Composite Terrane rocks. Offshore, less dense crust (< 2800 kg∙m−3) is found along the sedimentary basins of the Chukchi and Beaufort shelves. At LAB levels, there is a regional SE–NW trend that coincides with the current Pacific plate motion, with a lithospheric root underneath the Brooks Range, Northern Slope, and Chuckchi Sea, that may correspond to a relic of the Chukotka-Artic Alaska microplate. The obtained lithospheric root (above 180 km) agrees with the presence of a boundary of cold, strong lithosphere that deflects the strain towards the South. South of the Denali Fault the LAB topography is quite complex. East of 150 ° W, below Wrangellia and the eastern side of Chugach terranes, the LAB is much shallower than it is west of this meridian. The NW trending limit separating thinner lithosphere in the east and thicker in the ...